Effects of Low Frequency-Low Voltage Alternating Electric Current on Apoptosis Progression in Bioelectrical Reactor Biofilm - Hoseinzadeh, Edris; Wei, Chiang; Farzadkia, Mahdi; Rezaee, Abbas (Frontiers in Bioengineering and Biotechnology, 2020)
Bioelectrochemical systems (BESs) have undergone several modifications to promote enzymes or pathways used to reduce the energy required for microbial metabolism. When an electric current is applied intermittently, changes in dominant bacteria species, population, and growth rates take place. Applying electricity to bioelectrical reactor biofilms can stimulate cells or lead to cell death, and therefore, determination of the applied voltage range that leads to viable and stimulated bacteria is crucial. We investigated apoptosis progression induced by low frequency-low voltage alternating electric current (AC) in a bioelectrical reactor biofilm using indices discussed here. Our results showed that pHzpc for biofilms on the carbon cloth (CC) and stainless steel (SS) 304 electrodes was both at 8.67. The pHzpc for biofilms increased by 2 units compared to the inoculant bacteria mass. The Henderson-Hasselbalch equation reveals the cell wall compositions of biofilm formed on the CC and SS304 electrodes are exceedingly similar. In contrast, the CC and SS304 biofilm differ from raw sludge, indicating differences in the cell wall compositions of the present bacteria. The Fourier transform infrared spectroscopy (FTIR) spectra comparing biofilms to inoculation mass displayed differences in both shape and absorbance intensity, indicating that variability in the composition and quantity of each individual biofilm component. Based on the Michaelis-Menten model fitted to the experimental data, Vmax and Ks were determined to be 3.13 g Nitrate/d and 5.99 g Nitrate/L, respectively. In addition, dehydrogenase activity (DHA) content was variable under different applied voltages. The highest DHA was obtained at 8 Vpp and coincided with the highest rates of pollutant removal in comparison with other applied voltages. Flow cytometry analysis showed a relatively low number of apoptotic cells (10.93 ± 5.19%) for the studied AC amplitudes. It can be concluded that a low voltage-low frequency AC electric current induces significant changes in bacterial metabolic activity, but caused no significant change in their viability.